Skull Base Aerosol Generating Cases Amidst the COVID-19 Pandemic: An Experience from the Epicenter - Dastagirzada, Yosef; Klauberg, Olga; Sheerin, Kathleen; Lieberman, Seth; Lebowitz, Richard; McMenomey, Sean; Sen, Chandranath; Roland, J Thomas; Golfinos, John G.; Pacione, Donato (Journal of Neurological Surgery Part B: Skull Base, 2021)
Soon after the World Health Organization declared the severe acute respiratory syndrome coronavirus 2 a global health emergency on January 30, 2020, New York City was plagued by the virus and its health system and economy pushed to their limits. The majority of the limited neurosurgical data in relation to COVID-19 is anecdotal and the higher theoretical risk of transmission of the virus among skull base aerosol generating (SBAG) cases has not been investigated or discussed in a neurosurgical population. We discuss a series of 13 patients who underwent 15 SBAG surgical procedures during the peak of COVID-19 in our hospital system and the protocols use perioperatively for their procedures. Our data support that with proper preoperative testing, a well-delineated surgical algorithm, and appropriate personal protective equipment, emergent/urgent cases can be done safely in hospitals that are currently experiencing high volumes of COVID-19 cases as we did in March to May of 2020.
Keywords: COVID-19; coronavirus; pandemic; endoscopic endonasal approach; skull base surgery; personal protective equipment; neurosurgery; otolaryngology